Prevalence Of Coronary Heart Disease in An Urban Community of Varanasi - Sinha P.R; Gaur S.D; Somani P.N (Wolters Kluwer Medknow Publications, 1990)
An epidemiological study to find out the prevalence of coronary heart disease (CHD) and influence of well-known risk factors was conducted in an urban community. A total of 648 individuals over the age of 30 years were studied. The prevalence rate of CHD was 6.48%. The prevalence rate of CHD progressively increased with age in both sexes and was maximum in the age group of 60 years and above. Amongst the risk factors studied, CHD was directly related to the smoking habit (P) and diabetes mellitus (P). There was no correlation with socio- economic status (PO.05) and type of fat consumed in the diet (PO.05). CHD was inversely related to the physical activity (P)